Can you post the scale drawing please so I can help you
Move all terms that dont contain y to the right side and solve and you get:
y=4x/3-7
Hope this helps
Hello,
A=(4,2)
B=(2,8)
(AB)≡y-2=(x-4)*(8-2)/(2-4) ==> y=-3x+14
(BC)≡y-8=(x-2)*1/3 ==> y=1/3 x+22/3
This system can be a bit tricky unless you write it out:
(2n + 2)(2n - 2) ~ First you have to take one variable and multiply it to each of the other two variables, like:
2n * 2n ~ And:
2n * -2 ~ This gives you:
4n^2 - 4n
Now we do this with the other:
2 * 2n
2 * -2
4n - 4
Now we combine them both while adding like terms:
4n^2 - 4
Therefore your answer is: A. 4n^2 - 4
(This is due to how when having the positive 4n subtracted by the negative it cancels it out. Leaving us with the remaining two terms left.)
I hope this helps, have a great rest of your day! ^ ^
~Ghostgate
7+3x=2x+2
Send constants to one side and others to one side
3x-2x=2-7
x=-5